Utilisation of Social Media by Micro, Small and Medium Enterprises in Brunei Darussalam - Hashim, Nasshata Fatiha A.; Alek, Siti Kamaliah; Asmali, Khairunnisa Nurasikin; Rosli, Rafidah; Halim, Nurliyana Amalina Rabiatulafiqah Abdul; Almunawar, Mohammad Nabil (International Review of Management and Marketing, 2021)
Social media has increasingly become the new platform for conducting business activities, especially amongst Micro, Small and Medium Enterprises (MSMEs) on account of its practicality, relatively low costs, accessibility, and flexibility. Social media has transformed the business-to-customer relationship with regards to the empowerment of both sides of the relationship through increased participation, interaction, communication and most importantly, the control of information. This paper focuses on two social media platforms, namely Instagram and Facebook, in identifying the factors that promote the usage of social media by MSMEs in doing business activities. Based on the four objectives and hypotheses proposed in this study, an electronic questionnaire was conducted to find out how the effectiveness and interactivity factors significantly influence the use of social media and how social media will contribute to organisational performance and thus serve as competitive advantages for MSMEs in the context of Brunei Darussalam. Keywords: MSMEs; Social Media; Interactivity; Effectiveness; Organisational Performance; Competitive Advantage JEL Classifications: D91, L2 DOI: https://doi.org/10.32479/irmm.10906